Halal tourism based on local wisdom in Madura: Opportunities and challenges - Saifulloh Saifulloh; Betania Kartika; Mohamad Afiq bin Razali; Muhammad Aizat Jamaludin (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
Religious and spiritual tourism have been increasingly common and well-liked in recent decades, representing a large portion of global travel and expanding rapidly in recent years. The phrase "hidden paradise" is used to describe the island of Madura, which spans four regencies—Sumenep, Pamekasan, Sampang, and Bangkalan—and offers a variety of tourism opportunities, including historical tourism, natural tourism, cultural tourism, and religious tourism. This study aims to define halal tourism themes using conventional wisdom from the region. In this study, a case study with a qualitative descriptive methodology is used. In-depth interview and observation data were used as the primary sources, and books, the internet, and documentaries were used as the sources for the secondary data. According to the study, Madurese people have a limited comprehension of the idea of halal tourism and are therefore unable to implement it according to local wisdom.